What God can and cannot do: answers from the thaumaturgical horizon in the work of St. Augustine - Sottocorno, Estefania (Cuestiones Teológicas, 2024)
The purpose of this paper is to review Augustine’s reflection on thaumaturgic events, with the aim of clarifying their phenomenological characterization, their contrast with mere superstition, the impact they have to add followers to the horizon of Christian belief and/or to strengthen an already assumed faith. Likewise, we will seek to evaluate the theoretical-practical consequences that these facts may have in relation to the postulate of divine omnipotence in the framework of biblical and patristic theology. Our review takes as an anchor a series of testimonies on the thaumaturgic phenomena that are scattered in the immense Augustinian work, making them interact in order to highlight the fruitful perspective of this thinker in this regard and also to highlight the theoretical difficulties that the question of divine omnipotence brings with it in this specific area. As an adequate methodology to approach such testimonies, we propose to read these sources following the games of internal referral, but also in dialogue with the historical coordinates, especially in connection with the differentiated profiles of receivers that Augustine is assuming for diverse discursive structures, that is, more or less literate individuals, pagans or Christians, as we will see towards the end of our contribution. We will begin, instead, by examining the considerations relative to the more or less immediate effects that exceptional phenomena can have on the gnoseology of Christians -or potential Christians-, paying attention to the contrasts pointed out with respect to pagan superstitions, in order to observe how Augustine’s reflection in this regard leads us, almost naturally, to the question of divine omnipotence.
Keywords: Miracle; Omnipotence; Law; Superstition; Admiration; Persuasion; Faith; Reason; Martyrdom; Resurrection